PENGEMBANGAN KALIGRAFI DI INDONESIA: PERAN PESANTREN DAN PERGURUAN TINGGI DALAM MELESTARIKAN TRADISI DAN INOVASI SENI ISLAM - Tata Septayuda Purnama; Abdul Hafiz Muhamad Muklis; M. Ihsan Nashihin; Hanan Haqqani (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2026)
This study aims to analyze the development of Islamic calligraphy in Indonesia by highlighting the roles of Islamic boarding schools (pesantren) and universities in preserving tradition while promoting innovation in Islamic art. Calligraphy is understood not merely as the art of beautiful writing, but also as an intellectual, spiritual, and cultural heritage that occupies an important position within Islamic civilization. The research employs a qualitative approach using a case study method at the Pesantren Kaligrafi Al-Qur’an (LEMKA) in Sukabumi and the Department of Islamic Education, Al-Azhar Indonesia University. Data were collected through observation, in-depth interviews with instructors, practitioners, and institutional administrators, as well as documentation of various calligraphic activities and artworks. The study found that collaboration between Islamic boarding schools and universities has produced a complementary model of calligraphy development that integrates the strengths of tradition, scholarship, and technological innovation. This synergy represents an important strategy for ensuring the sustainability of Islamic calligraphy in Indonesia while expanding its relevance in the context of an increasingly digital society.